Implementation of Quantum Teaching Learning Strategies for Technician Training Program in Prima Data, Padang - Klara Septia Landa; Ismaniar Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
This research was motivated by the active phenomenon of computer technician training at the Prima Data Institute Padang in Padang. This is evidenced by the presence, attention, concentration and activity of student in the learning process. This study aims to look at the application of quantum teaching learning strategies at the prima data institute in padang. This research is quantitative descriptive reseach. The sampling technique used is simple random sampling. Samples were taken as much as 75% of the population so there were 15 people. The technique of collecting data uses a questionnaire. Data collection tool is a list of statements. The data analysis technique uses the percentage formula. The results showed that the quantum teaching learning strategy at the Prima Data Institute in Padang from the aspects of growth, natural, namai, demostrated, and celebrating the applied by the instructor is very good. This is evidenced by the majority of students giving statements always. Based on the results of the study, it was suggested that instructors continue to improve their activity and maintain quantum teaching learning strategies in computer technician training at the Prima Data Institute in Padang.Keywords: Quantum Teaching, Learning Activity